Malabou's Cineplastics and Contemporary French Film: Jacques Audiard, Céline Sciamma and Mia Hansen-Løve - Martin O’Shaughnessy (Film-Philosophy)
This article brings together the work of Catherine Malabou and films by Jacques Audiard, Céline Sciamma and Mia Hansen-Løve to probe what a Malabouian approach to cinema might be and how it could be brought into dialogue with specific works. Grounding itself in Malabou's thought around change, migration, metamorphosis and brain plasticity, it homes in on her discussion of cineplastics and the brain as image of the world and screen. It argues that, although the cineplastic is paradoxically not applied to film by Malabou, it constitutes a more productive route into film analysis than her direct cinematic references. Turning to the filmmakers to apply a cineplastic approach, it explores how they enable us to reflect on the mobile encounter between plastic subjects and their world, as the world reaches into them and shapes them and they reflexively respond by shaping themselves and reaching out into the world, moulding their relation to it. Building on the careful line Malabou draws between plasticity and neoliberal flexibility, the article uses her thought to probe the films' politics, finding most interest in their reflexivity, their capacity to render visible the contingency of apparently fixed forms and the non-reconciliation of filmic subjects to their worlds.